Liechtenstein : Assessment of the Supervision and Regulation of the Financial Sector Volume I-Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2003)
This report summarizes the assessment of Liechtenstein's compliance with internationally accepted standards for the regulatory and supervisory arrangements of the financial sector. It provides detailed assessments of Liechtenstein's implementation of international supervisory and regulatory standards relative to the Basel Core Principles (BCP) for effective banking supervision, International Association of Insurance Supervisors (IAIS) core principles for insurance Supervision, the International Organization of Securities Commissions (IOSCO) Objectives and Principles of Securities Regulation, and Financial Action Task Force Recommendations for antimoney laundering and combating the financing of terrorism.